2022
DOI: 10.3390/children9111776
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Soccer Training Effects on Pediatric Populations Physical Fitness and Health: A Systematic Review

Abstract: This systematic review analyzed the effects of recreational soccer programs on physical fitness and health-related outcomes in youth populations. Studies were sought in the following databases: (i) PubMed, (ii) Scopus, (iii) SPORTDiscus, and (iv) Web of Science. The eligibility criteria included (1) population: youth (<18 years old) populations with no restrictions on sex or health condition; (2) intervention: exposure to a recreational soccer training program of at least four weeks duration; (3) comparator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 92 publications
1
3
0
1
Order By: Relevance
“…organizations like the International Olympic Committee [18], UN Women [19], and UNESCO [20], advocating equal participation and empowerment in sports. The high participation rate in football (23.3%, Table 1) aligns with previous studies, confirming its global appeal and mass participation across diverse populations [21][22][23].This trend is particularly beneficial for adolescents, as previous studies have demonstrated that engagement in football can alleviate risk factors associated with overweight and obesity [24] while also enhancing various health indicators [25]. The study's findings regarding BMI indicate that a majority of the students (71.7%) had a normal BMI, reflecting a generally healthy population.…”
Section: Plos Onesupporting
confidence: 85%
“…organizations like the International Olympic Committee [18], UN Women [19], and UNESCO [20], advocating equal participation and empowerment in sports. The high participation rate in football (23.3%, Table 1) aligns with previous studies, confirming its global appeal and mass participation across diverse populations [21][22][23].This trend is particularly beneficial for adolescents, as previous studies have demonstrated that engagement in football can alleviate risk factors associated with overweight and obesity [24] while also enhancing various health indicators [25]. The study's findings regarding BMI indicate that a majority of the students (71.7%) had a normal BMI, reflecting a generally healthy population.…”
Section: Plos Onesupporting
confidence: 85%
“…Clemente и соавт., в котором автор делает вывод, что занятия в футбольных секциях улучшают общие параметры физической подготовленности, благоприятно влияют на сердечно-сосудистую систему футболистов и т.д. [20].…”
Section: обсуждение результатовunclassified
“…Current scientific findings underscore the efficacy of recreational soccer in positively influencing body composition and physical fitness across diverse age groups, particularly in young [ 19 ] and older populations [ 20 ]. However, there exists a notable gap in our understanding of the impact of recreational soccer on body composition and physical fitness in the critical transitional phase of young adulthood, characterized by the shift from high school to university.…”
Section: Introductionmentioning
confidence: 99%